A NEW SPECIES AND FIRST RECORD OF THE GENUS PTEROGLOSSA (ORCHIDACEAE: SPIRANTHINAE) FROM PERU - Damián, Alexander; Salazar, Gerardo A. (Phytotaxa, 2017)
The first species of the genus Pteroglossa is recorded from Peru. Pteroglossa acalcarata, a new orchid species from the eastern slope of the Peruvian Andes, is described and illustrated. It is similar in overall floral morphology to Pteroglossa macrantha, which is its closest relative according to a phylogenetic analysis of nucleotide sequences of plastid matK-trnK region presented here. However, P. acalcarata is distinguished from P. macrantha by its pubescent petals (vs. glabrous), inconspicuous lateral lobes of the labellum free from the sides of the column and absence of a spur.